2002
DOI: 10.1021/ol0267228
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Catalytic Activity of Nucleophilic N-Heterocyclic Carbenes for Transesterification Reactions

Abstract: [reaction: see text] Currently, there is a renewed interest in reactions that are catalyzed by organic compounds. Typical organic catalysts for acylation or transesterification reactions are based on either nucleophilic tertiary amines or phosphines. This communication discusses the use of nucleophilic N-heterocyclic carbenes as efficient transesterification catalysts. These relatively unexplored and highly versatile organic catalysts were found to be mild, selective, and more active than traditional organic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
151
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(156 citation statements)
references
References 13 publications
3
151
0
2
Order By: Relevance
“…Despite the well-established concept of asymmetric hydrogen bond catalysis [31][32][33][34] , NHCs have yet to identify themselves as good asymmetric Brønsted base catalysts for carbon-carbon bondforming reactions. Several transesterification reactions using NHCs have been reported, in which the carbene species were believed to exhibit Brønsted base characteristics [35][36][37][38][39] . Although transesterification of unactivated esters has been reported through the use of achiral NHC catalysts [35][36][37][38] , only highly reactive vinyl esters were successful in the asymmetric versions 39 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the well-established concept of asymmetric hydrogen bond catalysis [31][32][33][34] , NHCs have yet to identify themselves as good asymmetric Brønsted base catalysts for carbon-carbon bondforming reactions. Several transesterification reactions using NHCs have been reported, in which the carbene species were believed to exhibit Brønsted base characteristics [35][36][37][38][39] . Although transesterification of unactivated esters has been reported through the use of achiral NHC catalysts [35][36][37][38] , only highly reactive vinyl esters were successful in the asymmetric versions 39 .…”
mentioning
confidence: 99%
“…Several transesterification reactions using NHCs have been reported, in which the carbene species were believed to exhibit Brønsted base characteristics [35][36][37][38][39] . Although transesterification of unactivated esters has been reported through the use of achiral NHC catalysts [35][36][37][38] , only highly reactive vinyl esters were successful in the asymmetric versions 39 . Alternative nucleophile catalysis by NHC may occur for these reactions, as supported by recent work by Chi and co-workers 25,40,41 .…”
mentioning
confidence: 99%
“…In addition to the well-known umpolung transformations such as benzoin condensation 12,14 and Stetter reaction, 15 numerous other NHC-catalyzed reactions have been reported to date, e.g., transesterification, 16 ring-opening polymerization, 17 and the homoenolate reaction. 18 Previously, we reported on the use of the NHC-catalyzed aroylation of Cl-and sulfonyl substituted N-heteroarenes, 19 arylimidoyl chlorides, 20 and electron-deficient 4-fluorobenzenes 21 to afford keto derivatives, demonstrating the applicability of this transformation to a variety of N-heteroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] NHCs are now used as ligands for transition metals in many important chemical transformations such as Pd-catalyzed coupling reactions, 7) Ru-catalyzed olefin metathesis, 8) Rh-catalyzed hydrosilylations, [9][10][11] and Cu-catalyzed conjugate addition reactions. [12][13][14] Moreover, NHCs have attracted considerable attention as organocatalysts in several reactions such as benzoin condensation, [15][16][17][18][19][20] Stetter reaction, [21][22][23] transesterification/acylation reactions, 24,25) and nucleophilic substitution reactions. [26][27][28] In our study on the use of NHCs as ligands in organic transformations, we have recently reported the addition of diethylzinc to N-sulfonylarylimines catalyzed by Cu-NHC complexes, 29) where NHCs exhibit a strong ligand acceleration effect (LAE).…”
mentioning
confidence: 99%